Single-cell transcriptomics in metastatic breast cancer: mapping tumor evolution and therapeutic resistance - Han, Xu; Li, Xin; Bai, Ling; Zhang, Gangling (Frontiers in Genetics, 2025)
Metastatic breast cancer (MBC) remains the primary cause of mortality in breast cancer patients, driven by tumor heterogeneity, cellular evolution, and therapy-resistant clones. Traditional bulk transcriptomics, although informative, fail to capture rare subpopulations and context-specific gene expression, which are crucial for understanding disease progression. Single-cell transcriptomics (SCT) has emerged as a transformative approach, enabling high-resolution analysis of individual cells to reveal tumor composition, lineage dynamics, and transcriptional plasticity. This review highlights how SCT reshapes our understanding of MBC by mapping tumor evolution, identifying cancer stem-like cells, and characterizing states of epithelial-mesenchymal transition. We explore how SCT reveals clonal and spatial heterogeneity, and how tumor microenvironment components, including immune, stromal, and endothelial cells, interact with cancer cells to support immune evasion and the formation of a metastatic niche. SCT also uncovers mechanisms of therapeutic resistance, including transcriptional reprogramming and the survival of drug-tolerant subpopulations. Integrating SCT with spatial transcriptomics and multi-omics platforms offers a comprehensive view of the MBC ecosystem and may uncover novel therapeutic targets. We further discuss the translational potential of SCT for biomarker discovery, liquid biopsy development, and precision oncology. We address current technical challenges and future directions for clinical application. SCT is poised to transform MBC research and guide next-generation therapeutic strategies.